Differential effects of MDMA and scopolamine on working versus reference memory in the radial arm maze task - Kay, C.; Harper, D.N.; Hunt, M. (Neurobiology of learning and memory, 2010)
Previous research has suggested that the disruption to memory-task performance seen following acute exposure to 3,4-methylenedioxymethaphemtamine (MDMA) with rats might best be characterized as reference memory impairment rather than a working memory impairment. The current study specifically compared the effects of MDMA and scopolamine on measures of working versus reference memory in an eight-arm radial maze task. It was predicted that scopolamine would produce a greater impairment with respect to the working memory component of the task, whereas MDMA would produce a greater impairment to reference memory. On each trial rats were allowed to make a total of four arm visits in order to collect the reinforcers located at the end of different arms in the maze. Working memory errors were indicated by re-visiting an already visited arm during a trial, whereas visiting an arm that was never baited on any trial indicated a reference memory error. Using a within subjects design, rats were exposed to a range of doses of scopolamine and MDMA administered acutely. An interaction between drug type and memory error type was found. Specifically, scopolamine produced more working memory errors than reference memory errors, while MDMA produced the opposite pattern of significantly more reference memory errors compared to working memory error. This finding supported the hypothesis that MDMA disrupts reference memory processes in terms of an impairment in the strategies or rules used for solving memory tasks.